Terminal efficiency, lag and dropout in cohorts from 2007 to 2014 of dental students at the University of Costa Rica = Eficiencia terminal, rezago y abandono en las cohortes del2007 al 2014 de estudiantes de Odontología de laUniversidad de Costa Rica - Castro Sancho, Cristina 1970-
Determine the terminal efficiency, lag and dropout in the cohorts of students who entered the dentistry career at the Faculty of Dentistry at University of Costa Rica in the lapse 2007 to 2014. Data from 736 files were collected. The variables considered were sex, admission age, nationality, marital status, children, admission note, domicile and high school. The data was collected from the Student Application System, the physical files, and the data base from the Supreme Court of Elections of Costa Rica. Descriptive statistics, bivariate and multivariate analysis were made, which were implemented from two logistic regression models. 98% of the students were Costa Rican, 68% women, 79% entered according to the admission note, 43% entered with an age of 18 years or less, 50% came from a public school, 77% resided in the Greater Metropolitan Area and 95% were single and remained without children. The average terminal efficiency was 6%; 46% of students have graduated with lag, 16% are still enrolled and 32% dropped out. Sex, age, admission note, and motherhood are sociodemographic variables that are associated with terminal efficiency and dropout. The average terminal efficiency in the cohorts from 2007 to 2014 in the courses at the Faculty of Dentistry University of Costa Rica was very low, almost half of the students graduated with lag and about a third dropped out the studies. The grade from the admission note seems to be a predictor of students' academic behavior, higher grade had more chances of graduating and less likely to dropout.